2020
DOI: 10.3390/bios10030020
|View full text |Cite
|
Sign up to set email alerts
|

Surface Probe Linker with Tandem Anti-Fouling Properties for Application in Biosensor Technology

Abstract: This paper describes the anti-fouling capability of the novel monolayer-forming surface linker 3-(3-(trichlorosilylpropyloxy) propanoyl chloride (MEG-Cl). This compound was successfully attached to quartz crystal surfaces which are employed in an electromagnetic piezoelectric acoustic sensor (EMPAS) configuration. The MEG-Cl coated surface was both employed with Ni-NTA for the binding of recombinant proteins and for the tandem property of the avoidance of fouling from serum and milk. The MEG-Cl coated surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…MEG-Cl was synthesized according to previously published methods [28,29]. Anhydrous toluene and pyridine were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…MEG-Cl was synthesized according to previously published methods [28,29]. Anhydrous toluene and pyridine were purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Sufficiently high density of receptors not only provide higher sensitivity but also minimize undesirable interference of the analyte with the naked biosensor surface [26,27]. At the same time immobilization of antibodies using special linkers that provide antifouling surface properties is among the current trends in biosensor development [16]. The simplest method of Abs immobilization is physical adsorption (Figure 2A).…”
Section: Antibodies and The Methods Of Their Immobilization At Surfacesmentioning
confidence: 99%
“…In this respect, nucleic acid aptamers are ideal because they allow various chemical modifications that also improve their stability. It is also important to provide antifouling properties of biosensors for their application in complex liquids such as blood or blood plasma [16].…”
Section: Introductionmentioning
confidence: 99%
“…The EMPAS has been also used for the analysis of the interaction of milk and a serum with the surfaces of the crystals covered by antifouling layer. It has been shown that the layer composed of monolayer-forming surface linker 3-(3-(trichlorosilylpropyloxy) propanoyl chloride (MEG-Cl) provides excellent antifouling properties [ 57 ].…”
Section: Surface Acoustic Methodsmentioning
confidence: 99%